ANALISA DAN RANCANG BANGUN TEMPAT TIDUR BAYI ( BABY COT ) - Nurkim (KALPIKA, 2022)
The success of the national health insurance program (JKN) requires certainty of the availability of drugsupplies and medical devices from local industries. The limitation of the local medical device industry is anobstacle to the success of the program, and then released national program to accelerate the development ofthe independence of the national medical device industry. This research is intended to find an alternativeway to accelerate the development of the medical device industry by developing upstream technology,namely product design and development. With this technology, an effective way of developing medical deviceproducts for small industries will be obtained, the product reaches the market immediately, and meetsregulatory requirements. The product used in this case is a baby cot. The product development model used isto follow the regulatory requirements for good medical devices manufacturing practices (CPAKB), SNI ISO13485 and a systematic approach to design a product that is safe, and effective as intended use. Informationon product requirements and test methods is taken from EN 1130 Part 1 and Part 2. Using a systematicapproach the requirements and functions for the product can be analyzed. Furthermore, the embodimentdesign and detailed design are developed. The correctness of the design is proven by making functionalprototypes and verified by the stipulated design requirements. From this research, it was found a way todevelop medical device products for baby box products that are safe, and effective as intended use meetregulatory requirements.